Prophylactic Measures to Prevent Soft Tissue Abnormalities after Trauma - Sawhney, Raja; Sokoya, Mofiyinfolu; Ducic, Yadranko (Facial Plastic Surgery, 2017)
The goal of any reconstructive procedure is a complete return to premorbid form and function. Unfortunately, a return of pretraumatic form is routinely not considered during surgical planning. This leads to uncontrolled contracture of the soft tissue elements and permanent disfigurement. The goal of this article is to review interventions that improve soft tissue healing and long-term outcomes.
Keywords: facial trauma; cosmetic; deformity; midface lift; facial; wound contracture